Mobilisation of mesenchymal cells in cardiac patients: is intense exercise necessary?. Issue 3 (9th April 2008) - Lucia, A; De La Rosa, A; Silván, M Avila; López-Mojares, L M; Boraita, A; Pérez, M; Foster, C; García-Castro, J; Ramirez, M
Abstract : Circulating mesenchymal cells (cMCs) have a potential for regenerating damaged tissue, e.g., ischaemic myocardium. In patients (age range: 53–76 years) with stable coronary artery disease cMCs were determined before and after dynamic exercise of moderate (< respiratory compensation threshold (RCT)) (n = 9 patients) or high intensity (>RCT) (n = 11). Only high-intensity exercise (i.e., provoking signs of myocardial ischaemia in 3 patients and ventricular extrasystoles in another) induced a significant increase in cMCs (p = 0.009). These results support the hypothesis that intense exercise (near or at the point of myocardial ischaemia) is a potent stimulus for MC mobilisation.